Groundwater Select Proceedings of ICWEES-2016 (Water Science and Technology Library,, 2018)
This book comprises the select proceedings of the International Conference on Water, Environment, Energy and Society. The book is divided into three parts. The first part deals with some aspects of groundwater focusing on delineation of groundwater zones, spatio-temporal variability of groundwater, and aquifer vulnerability. The second part is on some aspects of groundwater recharge, dealing with recharge sources, management of recharge and recharge technology, change of land use / land cover on groundwater recharge. The concluding part covers groundwater quality, encompassing causes and sources of pollution, leachate migration, river bank filtration, variability of quality, assessment and management of quality. The book will be of interest to researchers and practitioners in the field of water resources, hydrology, environmental resources, agricultural engineering, watershed management, earth sciences, as well as those engaged in natural resources planning and management. Graduate students and those wishing to conduct further research in water and environment and their development and management will also find the book to be of value.